2013
DOI: 10.5603/cj.2013.0090
|View full text |Cite
|
Sign up to set email alerts
|

Optimal revascularization in diabetes after the FREEDOM trial: Were the controversies finally settled?

Abstract: (Cardiol J 2013; 20, 4: 331-336)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Finally, similar to the FREEDOM trial which clearly showed revascularization by CABG to be superior compared to PCI in patients with T2DM, our study which also showed CABG to be better than PCI in patients with ITDM, also suggests a comparative analysis of the new incoming stents which warrant further research [ 31 ].…”
Section: Discussionsupporting
confidence: 74%
“…Finally, similar to the FREEDOM trial which clearly showed revascularization by CABG to be superior compared to PCI in patients with T2DM, our study which also showed CABG to be better than PCI in patients with ITDM, also suggests a comparative analysis of the new incoming stents which warrant further research [ 31 ].…”
Section: Discussionsupporting
confidence: 74%